Efficient removal of toxic metal ions from wastewater using a recyclable nanocomposite: A study of adsorption parameters and interaction mechanism. (10th July 2017) - Alqadami, Ayoub Abdullah; Naushad, Mu.; Abdalla, Mohammad Abulhassan; Ahamad, Tansir; Abdullah ALOthman, Zeid; Alshehri, Saad M.; Ghfar, Ayman A.
Abstract: In this study, an effective and novel nanocomposite (Fe3 O4 @TAS) was prepared and applied for the removal of Cd(II), Cr(III) and Co(II) from liquid medium. The mechanism for the adsorption was elucidated by investigating the adsorption kinetics, isotherms and thermodynamics, thoroughly. The maximum adsorption capacities as found by the Langmuir model were 286, 370 and 270 mg g −1 for Cd(II), Cr(III) and Co(II), respectively. The structure, size, porosity and magnetic property, of the prepared magnetic nanocomposite were investigated by FT-IR, XPS, SEM-EDX, BET, XRD, HRTEM and VSM analyses. The saturation magnetization and BET surface area for Fe3 O4 @TAS were 41.4 emu g −1 and 210.34 m 2  g −1, respectively. Fe3 O4 @TAS was easily separated from aqueous solution using external magnet and it was regenerated by simple washing with 0.01 M HCl solution. The thermodynamic parameters showed that the involved process was spontaneous and exothermic. The findings inferred that Fe3 O4 @TAS had the efficiency in treating wastewater with coexisting metals such as Cd(II), Cr(III) and Co(II) metal ions. Graphical abstract: Highlights: Highly efficient and recyclable nanocomposite was synthesized. Nanocomposite was characterized by FTIR, XPS, SEM-EDX, BET, XRD, TEM and VSM analyses. The Qe were 286, 370 and 270 mg g −1 for Cd(II), Cr(III) and Co(II), respectively. Nanocomposite had a good BET surface area and a high saturation magnetization.